The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1115/1.4036665
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Control of Vibration in Single-Degree-of-Freedom Fractional Oscillators

Abstract: This paper proposes fractional sliding control designs for single-degree-of-freedom fractional oscillators respectively of the Kelvin-Voigt type, the modified Kelvin-Voigt type and Düffing type, whose dynamical behaviors are described by second-order differential equations involving fractional derivatives. Firstly, the differential equations of motion are transformed into non-commensurate fractional state equations by introducing state variables with physical significance. Secondly, fractional sliding manifold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Calculating the sum of sides of inequality for l ¼ 0 to infinity, it is concluded that condition equation (17) leads to upper-boundedness of cost as…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calculating the sum of sides of inequality for l ¼ 0 to infinity, it is concluded that condition equation (17) leads to upper-boundedness of cost as…”
Section: Resultsmentioning
confidence: 99%
“…Substituting equations (21) and (22) and the candidate Lyapunov function expressed in equation (19) and then substituting the calculated expression of candidate Lyapunov function in decreased condition (equation (17)), stabilization conditions (equation 23) are derived. The inclusion of system dynamics in the term i ðk þ lÞ results in viability of control scheme for the general class of considered nonlinear multibody dynamical system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the energy storage and dissipation properties of the Caputo fractionalorder derivatives, the expression of mechanical energy in single-degree-of-freedom fractional oscillators has been determined and energy regeneration and dissipation during the vibratory motion have been obtained in [22]. Vibration controls have been designed using sliding mode control technique and adaptive control technique for single-degree-of-freedom fractional oscillators, multi-degree-of-freedom fractional oscillators, and fractional Duffing oscillators in [23,24].…”
Section: Introductionmentioning
confidence: 99%